Ultrasound-Guided Morcellation During Holmium Laser Enucleation of the Prostate - Tzou, David T. (J Endourol Case Rep, 2018)
Background: Holmium laser enucleation of the prostate (HoLEP) has emerged as an accepted standard of care for the treatment of benign prostatic hyperplasia. This surgery relies on morcellation of the prostate adenoma once enucleation of the transition zone has been completed. Caution is required during this portion of the operation, as engaging bladder mucosa within the morcellator can result in bladder injury, a rare but potentially catastrophic complication of HoLEP. Morcellation of the prostatic tissue can be additionally challenging if visualization is poor from either equipment failure or increased bleeding from a highly vascularized prostate. Case Presentation: We report the case of a 66-year-old Caucasian man with an estimated 158 g prostate who underwent HoLEP at our institution. Enucleation was uneventful; however, upon placement of the nephroscope to begin morcellation, it was immediately evident that the lens of the nephroscope was damaged as there was extremely poor visualization. Without a replacement nephroscope available, this would have normally resulted in aborting the case and returning another day to complete the morcellation. Concurrent bladder ultrasonography was performed and allowed for additional visual feedback to the operator, helping guide the morcellator to safely engage the enucleated adenoma and complete the operation. Conclusion: This case report demonstrates the ability of performing the morcellation portion of HoLEP mainly with the visualization provided by concurrent bladder ultrasonography. By providing additional imaging feedback to the operator, ultrasound can be a complementary tool to assist in safely performing morcellation in situations of suboptimal cystoscopic visualization during HoLEP.